Novel miRNA-based drug CD5-2 reduces liver tumor growth in diethylnitrosamine-treated mice by normalizing tumor vasculature and altering immune infiltrate - Liu, Ken; Chen, Jinbiao; Zhao, Yang; Boland, Jade; Ting, Ka Ka; Lockwood, Glen; McKenzie, Catriona; Kench, James; Vadas, Mathew A.; Gamble, Jennifer R.; McCaughan, Geoffrey W. (Frontiers in Immunology, 2023)
Liver cancers exhibit abnormal (leaky) vasculature, hypoxia and an immunosuppressive microenvironment. Normalisation of tumour vasculature is an emerging approach to treat many cancers. Blockmir CD5-2 is a novel oligonucleotide-based inhibitor of the miR-27a interaction with VE-Cadherin, the endothelial-specific cadherin. The combination of a vasoactive medication with inhibition of immune checkpoints such as programmed cell death protein 1 (PD1) has been shown to be effective in treating liver cancer in humans. We aimed to study the effect of CD5-2 combined with checkpoint inhibition (using an antibody against PD1) on liver tumour growth, vasculature and immune infiltrate in the diethylnitrosamine (DEN)-induced liver tumour mouse model. We first analysed human data from The Cancer Genome Atlas for hepatocellular carcinoma and found high miR-27a and low VE-Cadherin were both significantly associated with poorer prognosis. CD5-2 and/or anti-PD1 antibody were given to the mice from age 7-months until harvest at age 9-months. Mice treated with CD5-2 plus anti-PD1 antibody had significantly smaller liver tumours (50% reduction) compared to mice treated with either agent alone, controls, or untreated mice. There was no difference in tumour number. Histologically, tumours in CD5-2-treated mice had less leaky vessels with higher VE-Cadherin expression and less tumour hypoxia compared to non-CD5-2-treated mice. Only tumours in the combination CD5-2 plus anti-PD1 antibody group exhibited a more favourable immune infiltrate (significantly higher CD3+ and CD8+ T cells and lower Ly6G+ neutrophils) compared to tumours from other groups. Thus, CD5-2 normalised tumour vasculature and reduced hypoxia in DEN-induced liver tumours. CD5-2 plus anti-PD1 antibody reduced liver tumour size possibly by altering the immune infiltrate to a more immunosupportive one.